PENGEMBANGAN MEDIA PUZZLE GEOMETRI UNTUK MENDESKRIPSIKAN, MENGURAI, DAN MENYUSUN BANGUN SEGIBANYAK KELAS IV SEKOLAH DASAR - Nimash Nailin Niam Faiqoh; Filia Prima Artharina; Bagus Ardi Saputro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a Polygon Geometry Puzzle learning media to help fourth-grade elementary school students describe, analyze, and arrange various polygonal shapes. The background of this study stems from students' difficulties in understanding the characteristics and shapes of flat shapes due to learning that is still centered on books and the limited availability of interesting concrete media. The puzzle media was developed using strong acrylic material and equipped with quartet cards containing pictures of shapes and their characteristics, equipped with QR Codes and Wordwall quizzes so as to increase student learning interest. This study uses the ADDIE model method which includes the stages of analysis, design, development, implementation, and evaluation. The development process involved validation from material experts, media experts, as well as teacher and student responses and tests. The validation results showed that this media met the feasibility of content, presentation, appearance, and ease of use. The practicality test showed that teachers and students gave very good responses because the media was easy to understand, interesting, and helped clarify the concept of polygonal shapes. The results of the study showed that the Geometry Puzzle media was able to improve students' understanding of the shapes and properties of polygons through interactive, concrete, and fun learning activities. This media was considered feasible and practical to be used as a mathematics learning aid, especially geometry material in elementary schools. Thus, this puzzle can be an alternative innovative learning media to support the achievement of student competencies.